Russian Translations of Writings of J.R.R. Tolkien as the Stage of their Cultural Reception in Russia - Shustova, Ellina V. (Journal of History Culture and Art Research, 2017)
This article identifies problems of translation of J.R.R. Tolkien`s works to the Russian language. Due to complexity of their reception in the Russian literature and culture, these problems continue at the present time. The purpose of this article is to consider the translational interpretations as a form of reception of J.R.R. Tolkien`s works in Russia and perform analysis of relevant stages of the receptive process. The leading approach to the study of this problem is the methodology of receptive aesthetics; this takes into account the development trends of the method. This research shows that it is the translation, in many respects, that sets trends for further understanding of writings by J.R.R. Tolkien in Russia and includes them in a Russian cultural and literary context, as well as set their level of systematic perception. Contents of this article may be used for readings in general and special courses for Western literature at universities, and may be useful to a wide range of readers interested in the work of J.R.R. Tolkien.